2015
DOI: 10.2105/ajph.2015.302712
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Cost-Related Medication Underuse Among Nonelderly Adults in a Nationally Representative Sample

Abstract: Objectives. We investigated whether nonelderly US adults (aged 18–64 years) in food-insecure households are more likely to report cost-related medication underuse than the food-secure, and whether the relationship between food insecurity and cost-related medication underuse differs by gender, chronic disease, and health insurance status. Methods. We analyzed data from the 2011 and 2012 National Health Interview Survey (n = 67 539). We examined the relationship between food insecurity and cost-related medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Despite the removal of adolescents and 2 provinces from our sample, the prevalence of cost-related nonadherence to prescription drugs was virtually the same as that reported by Law and colleagues 5 using the same data. Similar to findings from US-based studies, 16,21,22 after adjustment for confounders, we for respondents with and without prescription drug insurance by household food insecurity status; 332 respondents with missing insurance status were excluded from the analysis. Poisson regression with bootstrapped standard error was used, adjusting for household income, imputed income, income source, sex, age, Aboriginal status, housing tenure, household type, province of residence and number of different drugs prescribed.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the removal of adolescents and 2 provinces from our sample, the prevalence of cost-related nonadherence to prescription drugs was virtually the same as that reported by Law and colleagues 5 using the same data. Similar to findings from US-based studies, 16,21,22 after adjustment for confounders, we for respondents with and without prescription drug insurance by household food insecurity status; 332 respondents with missing insurance status were excluded from the analysis. Poisson regression with bootstrapped standard error was used, adjusting for household income, imputed income, income source, sex, age, Aboriginal status, housing tenure, household type, province of residence and number of different drugs prescribed.…”
Section: Discussionmentioning
confidence: 98%
“…This practice also hampers our ability to understand whether recruitment and outreach strategies are equally effective among different subpopulations of people who are food insecure. Secondary analyses of survey data and other population-based studies ( 4 , 13 ) contribute to this knowledge gap by failing to stratify participation in food assistance programs. Therefore, people who are food insecure may be inadvertently characterized as belonging to a monolithic population with homogeneous patterns of health care use, health status, and food assistance.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 47 studies found that lower level of education, racial discrimination, lack of social support, and poverty were factors in over one third of all deaths in the United States in 2000. 32 Food insecurity increases the likelihood of cost-related medication underuse, 33 which can lead to poorer health status. Poverty can also negatively impact patient health care utilization, as those who struggle financially may prioritize meeting their basic needs over seeking health care.…”
Section: Discussionmentioning
confidence: 99%